2003
DOI: 10.1590/s1678-77572003000100011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermocycling on the bond strength of a glass-infiltrated ceramic and a resin luting cement

Abstract: The aim of the present study was to evaluate the effect of thermocycling on the bond strength between the surface of the glass-infiltrated alumina ceramic In-Ceram (VITA) and the Panavia F resin cement (Kuraray CO.). Four 5x6x6mm In-Ceram blocks were obtained. One of the 6x6mm faces of each block was conditioned with Cojet - System (tribochemical silica coating, ESPE-3M) and then luted under a constant 750g pressure with Panavia F cement to another identical face of a resin composit block (Clearfil AP-X, Kurar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The results of the present study demonstrated that thermal cycling negatively influenced the quality of adhesive resistance, promoting the decrease in union values when the number of thermal cycles was increased. 14 38 41 42 43 44 Qualtrough et al . reported that there was a deterioration in marginal quality at the porcelain inlay/composite resin interface as a result of thermocycling.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study demonstrated that thermal cycling negatively influenced the quality of adhesive resistance, promoting the decrease in union values when the number of thermal cycles was increased. 14 38 41 42 43 44 Qualtrough et al . reported that there was a deterioration in marginal quality at the porcelain inlay/composite resin interface as a result of thermocycling.…”
Section: Discussionmentioning
confidence: 99%
“…These limits appeared to be safe for usage in clinical settings, and oral tissues were found to tolerate them well. Osvaldo et al [ 19 ] immersed their research samples in water for 30 seconds at a time at temperatures ranging from 5°C to 55°C, with a total of 200-37,500 warm cycles. For the previous analysis, instances were subjected to 1,000 intensity cycles at 5-55 °C with a 20-second stay length.…”
Section: Discussionmentioning
confidence: 99%
“…This led to the creation of two groups of samples with three assemblies of metallic blocks cemented to resin blocks, which were attached by cyanoacrylate adhesive (Super-Bonder, henkel ltda., Itapevi, SP, Brazil) to a cylindrical acrylic base connected to a machine especially designed by Andreatta Filho et al (2003) 1 for sectioning with carborundum discs measuring 0.15mm in thickness and 22mm in diameter, to the nearest 0.1mm.…”
Section: Methodsmentioning
confidence: 99%
“…The bond of resin compounds to metallic alloys has been improved during the past decades and several techniques have been developed in an attempt to achieve a stable bond. Sandblasting the metallic alloys with aluminum oxide is commonly employed for surface cleaning and a proper retentive topography, with a consequent increase in the adhesive bond 1,12,17 .…”
Section: Introductionmentioning
confidence: 99%